Effects of an Interdisciplinary Practice Bundle for Second-Stage Labor on Clinical Outcomes. Issue 4 (July 2018) - Garpiel, Susan J.
Abstract: Background: There is renewed interest in second-stage labor practices as recent evidence has challenged historical perspectives on safe duration of second-stage labor. Traditional practices and routine interventions during second-stage have uncertain benefit for low-risk women and may result in cesarean birth. Purpose: The purpose of this quality improvement project was to implement an interdisciplinary second-stage practice bundle to promote safe outcomes including method of birth and women's birth experience. Methods: Standardized second-stage labor evidence-based practice recommendations structured into a 5 Ps practice bundle (patience, positioning, physiologic resuscitation, progress, preventing urinary harm) were implemented across 34 birthing hospitals in the Trinity Health system. Results: Significant improvements were observed in second-stage practices. Association of Women's Health, Obstetric and Neonatal Nurses' perinatal nursing care quality measure Second-Stage of Labor: Mother-Initiated Spontaneous Pushing significantly improved [pre-implementation 43% (510/1, 195), post-implementation 76% (1, 541/2, 028), p < .0001]. Joint Commission Perinatal Care-02: nulliparous, term, singleton, vertex cesarean rate significantly decreased ( p = 0.02) with no differences in maternal morbidity, or negative newborn birth outcomes. Unexpected complications in term births significantly decreased in all newborns ( p < 0.001), and for newborns from vaginal births ( p = 0.03). Birth experience satisfaction rose from the 69th to the 81st percentile. Clinical Implications: Implementing 13 evidence-based second-stage labor practices derived from the Association of Women's Health, Obstetric and Neonatal Nurses and the American College of Nurse-Midwives professional guidelines achieved our goals of safely reducing primary cesarean birth among low-risk nulliparous women, and optimizing maternal and fetal outcomes associated with labor and birth. By minimizing routine interventions, nurses support physiologic birth and improve women's birth satisfaction. Abstract : In this quality improvement project, an interdisciplinary team from 34 birthing hospitals in one health system developed and implemented a second stage labor bundle to promote safer care for mothers and babies. The bundle was based on guidelines from the Association of Women's Health, Obstetric, and Neonatal Nurses and the American College of Nurse-Midwives. After implementation, there were improvements in clinical outcomes including a reduction in cesarean births and better patient satisfaction with the birth experience.